ACTS OF MISOGYNY AS REFLECTED IN CHO NAM JOO S KIM JIYOUNG BORN 1982 (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to reveal the acts of misogyny in the novel Kim Jiyoung Born 1982 by Cho Nam Joo This research uses qualitative research which is a research technique that stems from inductive thinking patterns that are based on participatory objective observation of a social phenomenon Data were taken from the novel using a feminist approach In addition the researcher used Anderson s modern misogyny analysis to reveal the acts of misogyny experienced by women in the novel Kim Jiyoung Born 1982 From this research it can be concluded that there are four acts of misogyny experienced by women in the novel Kim Jiyoung Born 1982 nbsp; The acts of misogyny are ambivalence toward women double standard discrimination and dislikeabilty of women < p>
Keywords: Misogyny, Act of Misogyny, Kim Jiyoung